Do elderly patients with non-small cell lung cancer get the best out of recent advances in first-line treatment? A comparative study in two tertiary cancer centers in Greece - Bakogeorgos, M.; Mountzios, G.; Bournakis, E.; Economopoulou, P.; Kotsantis, G.; Fytrakis, N.; Kouvatseas, G.; Dimopoulos, M.-A.; Kentepozidis, N. (Journal of Geriatric Oncology, 2015)
Background: Elderly patients with advanced non-small cell lung cancer (NSCLC) are thought to receive suboptimal treatment mainly due to concerns for poor compliance and/or excessive toxicity. Patients and Methods: Using the age of 70. years as the pre-defined cut-off, we compared elderly patients with advanced NSCLC suitable for first line chemotherapy with their younger counterparts in terms of: i) diagnosis and disease characteristics ii) adherence to treatment schedule, including dose intensity (DI), and relative dose intensity (RDI), iii) toxicity, tolerance, and efficacy outcomes. Results: Among 292 eligible patients, data were available for 245, of whom 107 (43.7%) belonged to the elderly group. This group was more likely to present with co-morbidities, non-smoking current status and diagnosis based on cytology alone. As compared to the non-elderly, elderly patients were more likely to receive single-agent therapy (8.0% vs. 29.2% respectively, p<. 0.001) and less likely to receive platinum-based chemotherapy (80.3% vs. 57.9%, p<. 0.001). Elderly patients also received docetaxel (24.3% vs. 40.4%), and bevacizumab (7.5% vs. 21.3%) significantly less often and received oral vinorelbine (24.3% vs. 11.8%) more frequently. Non-elderly patients were more likely to receive any of the cytotoxic drugs with RDI. >. 0.8 (49.6% vs. 33.0%, p=. 0.012) and RDI. >. 0.9 (29.6% vs. 16%, p=. 0.015). Substantial toxicity, as well as median overall survival did not differ significantly between the two groups. Conclusions: Only one third of the elderly patients received at least 80% of the scheduled treatment intensity. Nearly half received diagnosis based on cytology alone, which may deprive them from new, histology-driven, therapeutic approaches. © 2014 Elsevier Inc.
Keywords: Adherence; Chemotherapy; Efficacy; Elderly patients; NSCLC; Tolerance